2017
DOI: 10.1186/s12909-017-1010-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Smartphone application in medical education: a randomised trial (iSTART)

Abstract: BackgroundSmartphones are popular technologies that combine telephone communications and informatics in portable devices. Limited evidence exists regarding their effectiveness in improving academic performance among medical students. This study aims to assess whether a smartphone application could improve academic performance in multiple-choice tests.MethodsA double-masked randomised trial was held among interns at the School of Medicine of the Universidad de Valparaiso. Participants were randomised to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Therefore, ensuring MCQ are available in the long term and are available in a more readily accessible format may impact clinical training and education in a more meaningful manner. A study among medical interns demonstrated high participation rates and improved academic performance following use of a smartphone application for education . A similar approach may improve both participation rates and effectiveness of this novel CME tool.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, ensuring MCQ are available in the long term and are available in a more readily accessible format may impact clinical training and education in a more meaningful manner. A study among medical interns demonstrated high participation rates and improved academic performance following use of a smartphone application for education . A similar approach may improve both participation rates and effectiveness of this novel CME tool.…”
Section: Discussionsupporting
confidence: 89%
“…A study among medical interns demonstrated high participation rates and improved academic performance following use of a smartphone application for education. 24 A similar approach may improve both participation rates and effectiveness of this novel CME tool.…”
Section: Athavale and Murnionmentioning
confidence: 99%
“…Now healthcare professionals use smartphones for their daily activities (1,4). Smartphone technologies have combined telephone communications and informatics in portable devices (5,6). As a result of increased penetra-tion of smartphones, app usage is also growing, as these applications are projected to play a significant role in supporting education generally, particularly medical education (3).…”
Section: Introductionmentioning
confidence: 99%
“…This effort encourages rapidly developing software applications related to medicine. Currently, smartphones have various functions such as information searching, medical decision-making and educational applications [10]. For example, iSTART is a smartphone application that is used in medical education, a randomised trial as an evolution platform of IT in an educational application was proposed by [9].…”
Section: Introductionmentioning
confidence: 99%